Decline in Stroke Mortality Between 1997 and 2012 by Sex: Ecological Study in Brazilians Aged 15 to 49 Years - Laércio da Silva Paiva (Nature Portfolio, 2019)
Abstract This study aimed to analyse the time trends of stroke mortality between 1997 and 2012 according to sex in Brazilians aged 15 to 49 years. This ecological study used data obtained from the Mortality Information System, which is available from the National Health System Department of Informatics - DATASUS and maintained by the Brazilian Ministry of Health. Stroke definition included International Classification of Disease version 10 (ICD-10) codes I60, I61, I63, and I64. Crude and age-standardized mortality rates and respective 95% confidence intervals were estimated per 100,000 inhabitants and stratified by age, region, year, and sex. Linear regression models were used to analyse the time trends with a confidence level of 95%. The statistical program used was Stata 11.0. Between 1997 and 2012, there were 124,866 deaths due to stroke in Brazilians aged 15 to 49 years. There was a decreasing linear trend in stroke mortality among men (β = −0.46, p < 0.001, R2 = 0.95) and women (β = −0.40, p < 0.001, R2 = 0.98) during this period. Overall there was no significant difference in stroke mortality trends by sex, except with respect to the age group of 40 to 49 years where there was a difference in the decrease of stroke mortality between men and women (interaction sex * year: β = 0.238, p = 0.012, R² = 0.96). Mortality rates decrease significantly over time in men and women in the age group 15 to 49 years old, but there is only significant difference in the decrease of rates by sex only in the age group from 40 to 49 years old.